2023
DOI: 10.1029/2023gl106941
|View full text |Cite
|
Sign up to set email alerts
|

Energy Conversion by a Twisted Magnetic Structure at Magnetopause Boundary Layer: MMS Observations

C. X. Du,
H. S. Fu,
Z. Wang
et al.

Abstract: The Earth's magnetopause is an ion‐scale boundary that separates the magnetosphere from the shocked solar wind. At such boundary, energy‐conversion processes frequently occur. Previous studies suggested that such energy conversions are related to the magnetic reconnection process. Here, we report a new mechanism that the coaction between the twisted magnetic structure and lower‐hybrid waves can also drive energy conversion (J⋅ E, J is current density and E is electric field) at the magnetopause boundary layer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Recently, Du et al (2023) have used a reconstruction method named as FOTE at the magnetopause to reveal that strong current filaments are driven by the twist of the local magnetic field. In our two events (Figures 2 and 3), it can be observed that they are also associated with strong current filaments in their vicinity; similar characteristics are prevalent in the events we tallied.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Du et al (2023) have used a reconstruction method named as FOTE at the magnetopause to reveal that strong current filaments are driven by the twist of the local magnetic field. In our two events (Figures 2 and 3), it can be observed that they are also associated with strong current filaments in their vicinity; similar characteristics are prevalent in the events we tallied.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Strong currents generally correspond to strong magnetic field variations, and twist magnetic is a type of strong magnetic field variation, but it is necessary to check whether it corresponds to a twisted magnetic structure using the FOTE method (Fu et al 2015). The findings of Du et al (2023) have provided some new ideas and insights for us to explore the formation of SFACs. We will conduct further analysis on our events in the future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%